2005
DOI: 10.1130/b25510.1
|View full text |Cite
|
Sign up to set email alerts
|

Semiannual patterns of erosion and deposition in upper Monterey Canyon from serial multibeam bathymetry

Abstract: Recently acquired 3-m-resolution 244 kHz multibeam seafl oor bathymetry (0.5 m depth precision) reveals geomorphology at suffi cient detail to interpret small-scale features and short-term processes in the upper 4 km of Monterey Canyon, California. The study area includes the continental shelf and canyon features from 10 m to 250 m depth. The canyon fl oor contains an axial channel laterally bounded by elevated complex terrace surfaces. Sand waves with 2 m height and 35 m average wavelength dominate the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 13 publications
3
115
0
1
Order By: Relevance
“…The canyon head comes within 0.1 to 0.2 km of the shoreline (Table 2), sand is fed into the upper reaches of the canyon primarily by longshore drift with subordinate direct fluvial input (Smith et al 2005), and current meters indicate that turbidity flows competent to transport sand in Monterey Canyon are commonly triggered by winter storms (Paull et al 2003).…”
Section: Gravel-floored Canyonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The canyon head comes within 0.1 to 0.2 km of the shoreline (Table 2), sand is fed into the upper reaches of the canyon primarily by longshore drift with subordinate direct fluvial input (Smith et al 2005), and current meters indicate that turbidity flows competent to transport sand in Monterey Canyon are commonly triggered by winter storms (Paull et al 2003).…”
Section: Gravel-floored Canyonsmentioning
confidence: 99%
“…With improved technology for imaging the sea floor, and the deployment of current monitors and sediment traps in some submarine canyons, the scale and distribution of these canyons has become better defined and their role as conduits for transferring sediment from terrestrial sources into the deep basin has become better understood (e.g., Piper and Savoye 1993;Khripounoff et al 2003;Paull et al 2003;Smith, et al 2005;Oliveira et al 2007;Harris and Whiteway 2011). Indeed, as observed by Normark and Carlson (2003), every major submarine fan in the world is fed by a submarine canyon.…”
Section: Introductionmentioning
confidence: 99%
“…Such offsets are common in difference analyses of steeply sloping features (cf. Smith et al 2005;Hughes Clarke et al 2009), and are particularly evident when data are not collected using RTK positioning (this study). That such artifacts exist even in studies using high-quality modern swath bathymetry data underscores the need for caution when interpreting "change" among datasets of varying resolution and quality, especially in areas with complex seafloors.…”
Section: Long-term Bathymetrymentioning
confidence: 97%
“…For example, Maria Ferdin was senior author on a research paper that identified a new indicator species for the detection of domoic acid in California coastal waters (Ferdin, et. al., 2002); Kate Thomas was senior author on a research paper that analyzed the effects of human activity on the foraging behavior of sanderlings (Thomas et al, 2003); Greg Ruiz coauthored a paper on erosion and deposition in a submarine canyon using serial multibeam bathymetry (Smith et al, 2005); Erica Morris coauthored a paper on genus-specific marine habitat mapping using high-resolution multibeam bathymetry (Iampietro et al, 2005); and Ryan Lockwood coauthored a paper on mapping the geothermal surface heat flux from Yellowstone National Park (Watson et al, in press). …”
Section: Elements Of the Essp Pyramidmentioning
confidence: 99%